Psychoeducational Interventions on Improving Caring Behavior for Families of People With Mental Disorders at The Public Health Center of Negara Batin - Feri Agustriyani; Andi Susanto; Suwarni Suwarni; Hamid Mukhlis (Universitas Aisyah Pringsewu, 2022)
Treatment for people with mental disorders (ODGJ) includes not only pharmacological treatment, but also environmental-based treatment. The closest environment is family. One of the obstacles in healing for people with mental disorders (ODGJ) is the low participation of families in caring for people with mental disorders (ODGJ) at home and the lack of family and community knowledge about mental illness. This creates a negative stigma aimed at people with mental disorders (ODGJ) which results in neglect, exclusion, harassment, violent behavior, shackles, discrimination, and other violations of ODGJ's human rights. The family as caregiver must be able to care for and assist people with mental disorders (ODGJ) in living their daily lives. However, the role played by the family is still not optimal so it is necessary to provide psychoeducational intervention. Psychoeducation is important to strengthen caring for caregivers when caring for people with mental disorders (ODGJ). The research objective was to determine the increase in caring behavior of people with mental disorders (ODGJ) families after being given psychoeducational intervention. This research was a quasi-experimental one group pre post test study with a sampling technique using simple random sampling, the sample in this research was 40 families with people with mental disorders (ODGJ). The results showed that p = 0.03 with a (0.05) meaning that there was an increase in the caring behavior of the people with mental disorders(ODGJ) family after being given psychoeducational intervention. Psychoeducation is an intervention that can be given not only to groups but also individually so that information on how to care and motivation for independence of family members with mental disorders can be well received by the family and can be applied in the care of people with mental disorders at home. Abstrak: Pengobatan pada ODGJ tidak hanya meliputi farmakologis saja, tetapi juga pengobatan berbasis lingkungan. Lingkungan terdekat adalah keluarga,. Salah satu kendala dalam penyembuhan pada ODGJ adalah rendahnya partisipasi keluarga dalam hal perawatan ODGJ dirumah serta kurangnya pengetahuan keluarga dan masyarakat tentang penyakit jiwa. Hal ini memunculkan stigma negatif yang ditujukan pada ODGJ yang berakibat pada penelantaran, pengucilan, pelecehan, perilaku kekerasan, pemasungan, diskriminasi, dan pelanggaran hak azasi ODGJ lainnya. Keluarga sebagai caregiver harus mampu merawat dan mendampingi ODGJ menjalani kehidupan sehari-hari. Namun peran yang dijalani keluarga masih belum optimal sehingga perlu diberikan intervensi psikoedukasi. Psikoedukasi menjadi penting untuk memperkuat caring pada caregiver ketika merawat ODGJ. Tujuan penelitian ini untuk mengetahui peningkatan perilaku caring keluarga ODGJ setelah diberikan intervensi psiokoedukasi.Penelitian ini merupakan penelitian quasy eksperiment one grup pre post test dengan tehnik pengambilan sampel menggunakan simple random sampling, sampel pada penelitian ini sebanyak 40 keluarga dengan ODGJ. Hasil penelitian menunjukkan nilai p=0,03 dengan a(0,05) artinya adanya peningkatan perilaku caring keluarga ODGJ setelah diberikan intervensi psikoedukasi. Psikoedukasi merupakan intervensi yang dapat diberikan tidak hanya pada kelompok saja tetapi juga secara individu supaya informasi cara perawatan dan motivasi kemandiriananggota keluarga yang mengalami gangguan jiwa dapat diterima dengan baik oleh keluarga dan dapat diterapkan dalam perawatan orang dengan gangguan jiwa dirumah.